SUN-LB63 Optic Disc Edema in Patients With Craniofacial Fibrous Dysplasia / McCune-Albright - Raborn, Layne (J Endocr Soc, 2020)
Background: Fibrous Dysplasia (FD) is a mosaic disorder that involves fibro-osseous lesions in bone. In the presence of coexisting extra-skeletal features, it is termed McCune-Albright Syndrome (MAS). Optic disc edema (ODE) is a potentially serious finding that may progress to optic disc ischemia and nerve atrophy. We sought to determine the prevalence and identify risk factors for the development of ODE in the NIH FD/MAS cohort. Methods: A retrospective review was conducted and identified 7 patients with craniofacial FD/MAS with a diagnosis of ODE. Controls were patients with a normal eye examination and without potentially confounding ophthalmologic conditions. The cohort consisted of 73 patients with craniofacial FD, 7 (10%) of whom were diagnosed with ODE. Results: Radiographic and statistical analysis identified Chiari I malformation (CM1) and mass lesions, including aneurismal bone cysts (ABCs) and arachnoid cysts, as significant risks for developing ODE (odds ratio [OR] 48.8; 95% confidence interval [CI], 5.3 to 633.1; p < 0.01) and (OR 16.3; 95% CI, 2.8 to 81.9; p <0.01) respectively. There was no significant association of ODE with endocrinopathies, medications, optic canal diameter or intracranial volume.Conclusion: ODE can be found in association with craniofacial FD and may be the initial presenting symptom of intracranial mass lesions or CM1, which has previously been shown to be at an increased prevalence in the FD/MAS cohort. Patient with craniofacial FD/MAS and intracranial mass lesions or CM1 are at an increased risk of developing ODE and require close monitoring.